The Four Little Chicks - Williams, Yinka (University Press Plc, 2001)
Mother Hen tries to train her chicks to be gentle and well-behaved.Yellow chick seems to think differently.His behaviour nearly lands the whole brood in a disaster.
Keywords: Juvenile literature-Fiction